2006
DOI: 10.1007/s00330-006-0451-7
|View full text |Cite
|
Sign up to set email alerts
|

Placement of endovascular stent-grafts for emergency repair of acute traumatic aortic rupture: a single-centre experience

Abstract: The aim of this retrospective study was to evaluate mid- and long-term results of endovascular stent-graft placement for emergency repair of acute traumatic thoracic aortic rupture. From 1996 through 2005, 22 consecutive patients (mean age: 38.7 years) underwent endovascular repair of acute traumatic thoracic aortic rupture located at the aortic isthmus in most cases. All patients were at high surgical risk due to severe associated injuries. The endografts were inserted via femoral or iliac artery access under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 44 publications
(60 reference statements)
2
10
0
Order By: Relevance
“…9,11,12,18,24,25,[36][37][38][39][42][43][44] Fig 3). 6,9,11,12,[14][15][16][17][18][19][20][21][22][23][24][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][45][46][47][48] Again, there was no evidence of heterogeneity (Cochran Q, 10.74; P ϭ .99) or bias (Egger 0.10; P ϭ .50). However, no significant difference was noted in the risk of SCI with LSA coverage and preoperative revascularization compared with no LSA coverage (0.8% vs 2.7%, respectively; POR, 1.69; 95% CI, 0.56-5.15; P ...…”
Section: Resultsmentioning
confidence: 98%
“…9,11,12,18,24,25,[36][37][38][39][42][43][44] Fig 3). 6,9,11,12,[14][15][16][17][18][19][20][21][22][23][24][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][45][46][47][48] Again, there was no evidence of heterogeneity (Cochran Q, 10.74; P ϭ .99) or bias (Egger 0.10; P ϭ .50). However, no significant difference was noted in the risk of SCI with LSA coverage and preoperative revascularization compared with no LSA coverage (0.8% vs 2.7%, respectively; POR, 1.69; 95% CI, 0.56-5.15; P ...…”
Section: Resultsmentioning
confidence: 98%
“…Of the type I endoleaks, three resulted in the deaths mentioned earlier (38,53,58). Eleven were successfully treated with additional stent-grafts (22,54,55,62,66,67,71), one with an uncovered Palmaz stent (Cordis) (51), and two with balloon dilation (67). There were five cases of open conversion (39,63,66,71) and five cases of spontaneous thrombosis (29,34,38,42,74).…”
Section: Case Seriesmentioning
confidence: 93%
“…11,12 It has long been observed that severe angulation and curvature in the abdominal aorta can result in endoleaks when treating aneurysms. 13 Near the aortic arch, the geometry can be severely curved or angulated, rendering sealing of the PIT a challenge.…”
Section: Clinical Perspective See P 112mentioning
confidence: 99%